I. A. [Isaak August] Dorner (Tufts Archival Research Center, 2008)
2.5 x 4.25. "I. A. Dorner." Produced by: Loescher & Petsch, Berlin, Atelier, Leipziger-Strase 132, Eingang im Mittel-Portal. These dates are approximate.